Associations between cagA, vacA, and the clinical outcomes of Helicobacter pylori infections in Okinawa, Japan - INAGAKI, TOMOKO (Kobe J Med Sci, 2017)
Helicobacter pylori, which is involved in the pathogenesis of gastroduodenal disease, produces CagA and VacA as major virulence factors. CagA is classified into East Asian and Western types based on the number and sequences of its Glu-Pro-Ile-Tyr-Ala motifs. The vacA gene has three polymorphic regions: the signal (s), intermediate (i), and middle (m) regions. The lowest gastric cancer mortality rate is seen in Okinawa. On the Japanese mainland (Honshu), most H. pylori produce s1/m1-VacA, which exhibits strong toxicity, and East Asian-type CagA. However, the H. pylori detected in Okinawa produces s1/m2-VacA, which exhibits weak toxicity, or s2/m2-VacA, which is non-toxic, and Western-type CagA. Studies about the i-region of vacA have been performed around the world, but there have been few such studies in Japan. Therefore, the aim of this study was to assess the relationships between the clinical outcomes of H. pylori infections in Okinawa, vacA (especially the i-region genotype), and cagA. H. pylori strains that were collected from patients with gastric cancer or gastric ulcers in Okinawa only produced the i1-type VacA virulence factor. The vacuolating cytotoxin activity of i1-type VacA was stronger than that of i2-type VacA, suggesting that the i-region genotype of vacA is closely associated with vacuolating cytotoxin activity. These results indicate that the i-region genotype of vacA is a useful marker of both H. pylori virulence and the clinical outcomes of H. pylori infections in Okinawa, Japan.